Effectiveness of Subacromial Anti-Adhesive Agent Injection after Arthroscopic Rotator Cuff Repair: Prospective Randomized Comparison Study - Oh, Chung Hee; Oh, Joo Han; Kim, Sae Hoon; Cho, Jae Hwan; Yoon, Jong Pil; Kim, Joon Yub (Clinics in orthopedic surgery, 2011)
Arthroscopic rotator cuff repair generally has a good clinical outcome but shoulder stiffness after surgery due to subacromial adhesion is one of the most common and clinically important complications. Sodium hyaluronate (HA) has been reported to be an anti-adhesive agent in a range of surgical procedures. However, there are few reports of the outcomes of arthroscopic rotator cuff repair of the shoulder. This study examined whether a subacromial injection of HA/carboxymethylated cellulose (CMC) affected the postoperative shoulder stiffness and healing of rotator cuff repair, as well as the safety of an injection. Between January 2008 and May 2008, 80 consecutive patients with arthroscopic rotator cuff repair were enrolled. The patients were assigned randomly to the HA/CMC injection group (n = 40) or control group (n = 40). All patients were evaluated using the visual analog scale (VAS) for pain, passive range of motion at 2, 6 weeks, 3, 6, 12 months after surgery, and the functional scores at 6, 12 months postoperatively. Cuff healing was also evaluated using CT arthrography or ultrasonography at 6 or 12 months after surgery. The HA/CMC injection group showed faster recovery of forward flexion at 2 weeks postoperatively than the control group but the difference was not statistically significant (p = 0.09). There were no significant difference in pain VAS, internal rotation, external rotation and functional scores between two groups at each follow-up period. The functional scores improved 6 months after surgery in both groups but there were no differences between the two groups. The incidence of unhealed rotator cuff was similar in the two groups. There were no complications related to an injection of anti-adhesive agents including wound problems or infections. A subacromial injection of an anti-adhesive agent after arthroscopic rotator cuff repair tended to produce faster recovery in forward flexion with no adverse effects on cuff healing. However, its anti-adhesive effects after rotator cuff repair should be considered carefully with further studies.